2002
DOI: 10.1159/000048599
|View full text |Cite
|
Sign up to set email alerts
|

Single-Nucleotide Variant in Multiple Copies of a Deleted in Azoospermia (DAZ) Sequence – a Human Y Chromosome Quantitative Polymorphism

Abstract: The evolution of the deleted in azoospermia (DAZ) gene family supports prevalent theories on the origin and development of sex chromosomes and sexual dimorphism. The ancestral DAZL gene in human chromosome 3 is known to be involved in germline development of both males and females. The available phylogenetic data suggest that some time after the divergence of the New World and Old World monkey lineages, the DAZL gene, which is found in all mammals, was copied to the Y chromosome of an ancestor to the Old World… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2002
2002
2017
2017

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 21 publications
1
3
0
Order By: Relevance
“…Recent studies have identified a number of miRNAs that are significantly upregulated in human testis, spermatozoa, and seminal plasma 33 , and more than 80 genes have been identified as essential for male infertility in humans and mice 34 . Genes on the Y chromosome have been emphasized because of observed microdeletions in patients; in addition, genes such as DAZ and HSFY, which were also discovered in our results, have been examined as possible susceptibility genes for azoospermia 35 36 . Our comparative analysis revealed a large number of deregulated genes.…”
Section: Discussionsupporting
confidence: 63%
“…Recent studies have identified a number of miRNAs that are significantly upregulated in human testis, spermatozoa, and seminal plasma 33 , and more than 80 genes have been identified as essential for male infertility in humans and mice 34 . Genes on the Y chromosome have been emphasized because of observed microdeletions in patients; in addition, genes such as DAZ and HSFY, which were also discovered in our results, have been examined as possible susceptibility genes for azoospermia 35 36 . Our comparative analysis revealed a large number of deregulated genes.…”
Section: Discussionsupporting
confidence: 63%
“…Thus far, more than 80 genes have been identified as essential for male infertility in humans and mice [ 3 ]. Genes on the Y chromosome were emphasized because of observed microdeletions in patients, and genes such as DAZ and HSFY were examined for possible susceptibility genes [ 28 , 29 ]. Recently, homozygous mutation of the aurora kinase C gene was identified in large-headed multiflagellar polyploid spermatozoa, a rare form of infertility, using homozygosity mapping [ 30 ].…”
Section: Discussionmentioning
confidence: 99%
“…The limits of this technique have thus been demonstrated, although there may still be some qualitative interest [11]. Moreover, some of these SNVs (sY581 for example) proved to be useful polymorphisms for population genetic studies [23,24].…”
Section: Choice Of the Q-pcr Techniquementioning
confidence: 99%